Structural insights into the C-terminus of the histone-lysine N-methyltransferase NSD3 by small-angle X-ray scattering - Belviso, Benny Danilo; Shen, Yunpeng; Carrozzini, Benedetta; Morishita, Masayo; di Luccio, Eric; Caliandro, Rocco (Frontiers in Molecular Biosciences, 2024)
NSD3 is a member of six H3K36-specific histone lysine methyltransferases in metazoans. Its overexpression or mutation is implicated in developmental defects and oncogenesis. Aside from the well-characterized catalytic SET domain, NSD3 has multiple clinically relevant potential chromatinbinding motifs, such as the proline-tryptophan-tryptophan-proline (PWWP), the plant homeodomain (PHD) and the adjacent Cys-His-rich domain located at the C terminus. The crystal structure of the individual domains is available and this structural knowledge has allowed designing of potential inhibitors, but the intrinsic flexibility of larger constructs has hindered the characterization of mutual domain conformations. Here we report the first structural characterization of the NSD3 C-terminal region comprising PWWP2, SET, and PHD4 domains, which has been achieved at low resolution by using solution small-angle X-ray scattering (SAXS) data on two multiple-domain NSD3 constructs complemented with size-exclusion chromatography and advanced computational modeling. Structural models predicted by machine learning have been validated in direct space, by comparison with the SAXS-derived molecular envelope, and in reciprocal space, by reproducing the experimental SAXS profile. Selected models have been refined by SAXS-restrained molecular dynamics. This study shows how SAXS data can be used with advanced computational modeling techniques to achieve a detailed structural characterization and sheds light on how NSD3 domains are interconnected in the C-terminus.